Hormonal and metabolic effects of carbohydrate restriction in children with Prader‐Willi syndrome. (31st January 2019) - Irizarry, Krystal A.; Mager, Diana R.; Triador, Lucila; Muehlbauer, Michael J.; Haqq, Andrea M.; Freemark, Michael
Summary: Objective: Macronutrient regulation of hyperphagia and adiposity in Prader‐Willi syndrome (PWS) is poorly understood. We compared fasting and postprandial concentrations of hormones and metabolites in eight PWS children (age 9‐18 years) fed, in random order, low carbohydrate, high‐fat (LC, 15% carb; 65% fat; 20% protein) and low‐fat, high carbohydrate (LF, 65% carb, 15% fat, 20% protein) diets matched for calories and protein. Methods: Participants were randomized to consume either the LC or LF diet during a first hospital admission and the second diet during a subsequent admission. Blood samples were obtained after overnight fasting and 1 hour after a mixed meal. Results: Relative to subjects consuming the LF diet, subjects consuming the LC diet had: lower postprandial insulin concentrations ( P = 0.02); higher fasting GLP‐1 AND GIP concentrations and increased postprandial GLP‐1 ( P < 0.02); reduced ratio of fasting ghrelin to GLP‐1 ( P = 0.0078); increased FFA and fatty acid oxidation, as assessed by concentrations of even‐chain acylcarnitines ( P < 0.001); lower fasting TG and TG/HDL ratio ( P < 0.01); and higher concentrations of branch chain amino acids ( P < 0.01). There were no changes in glucose, PYY, or adiponectin. CRP, AST and ALT were all higher ( P < 0.01) on the LC diet. Conclusions: Increases in GLP‐1 with low carbohydrate feeding and reductions in the ratio of ghrelin to GLP‐1 might limit food intake and improve glycaemic control in PWS. Other potential benefits of carbohydrate restriction may include fat mobilization and oxidation and reductions in the TG/HDL ratio, a marker of insulin resistance. However, increases in CRP, AST and ALT necessitate longer‐term studies of low carbohydrate efficacy and safety.